HPV vaccination worldwide and in Poland: successes, gaps, and the critical role of nursing practice - Gniadek, Zofia; Bajor, Gabriela; Jurczyk-Florkiewicz, Wiktoria; Machno, Patrycja; Pszczółka, Agata; Kozak, Joanna; Melka, Kacper; Szulewski, Mikołaj; Salagierska, Aleksandra; Matuszczak, Patryk (Nursing Problems / Problemy Pielęgniarstwa, 2026)
Human papillomavirus (HPV) infection is one of the most common sexually transmitted infections and a major cause of cervical, anogenital, and oropharyngeal cancers. Prophylactic HPV vaccination is a key element of primary prevention, with nurses playing an important role in vaccine delivery and health education. This narrative review aims to summarise current evidence on HPV infection and vaccination, with particular emphasis on nursing practice. A narrative review of literature from PubMed, Scopus, and Web of Science (1999-2025) was conducted. Additionally, official epidemiological data from national and international public health institutions were analysed. Evidence from countries with established vaccination programmes shows a significant reduction in HPV-related diseases. In Poland, vaccination coverage remains insufficient despite the introduction of a national programme. Strengthening the educational and preventive role of nurses is essential to improve vaccination uptake and reduce the burden of HPV-related cancers.